Berwirausaha Batik Ecoprint: Pelatihan dan Pendampingan pada Darma Wanita Dinas Pangan, Pertanian, dan Perikanan Kota Balikpapan - Miswaty Miswaty; Tutik Yuliani; Nawang Retno Dwiningrum; Hasrullah Hasrullah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
Entrepreneurship is one of the driving forces of the economy in a household and can be used to improve the economy in an area. The more people who have the passion and desire in entrepreneurship will be able to create jobs and reduce unemployment so that the economy in an area will increase. To be able to have an entrepreneurial spirit, a creative and innovative thinking is needed in running a business,. At this time batik which is one of the inheritances from our ancestors is starting to be favored by all people for various things including for modern clothing, interior goods. Therefore need to create creative works of art by exploring and combining ecoprint and batik techniques into textile artworks. In this service activity, we try to provide training on making ecoprint batik by utilizing existing natural resources, namely leaves by going through various stages, namely: the mordanting stage, sketching, steaming, lifting and cooling the fabric, color locking and drying. This training was attended by women from the Department of Food, Agriculture, and Fisheries of Balikpapan City. The results of this service show that the training participants are enthusiastic about taking the training seriously, which is shown by the participants following from beginning to end and they practice how to make ecoprint at the training site.